Amateur football map (4th league) from Romania generated by the coronavirus (COVID-19) in the pre-pandemic season (2019/2020) - Alexandru ILIEȘ; Jan A. WENDT; Oliver DEHOORNE; Codruț G. BULZ (Editura Universităţii din Oradea, 2021)
After the 2nd World War, for the first time after 7 decades, sports in general, and amateur football in particular, are facing a new global challenge generated by the coronavirus (COVID-19) pandemic. Pre-pandemic football season 2019/2020 held on the field only for the first part (690 teams; 781 games), was suspended at the beginning of March, 2020. This situation generated an uncertain 5-month break until the first official games in play-offs (1-9 August, 2020) in wich only 46 teams (6.6%) in total actually participated. In a state of global uncertainty, to the suggestion of RFF, the 42 county football associations were "invited" to identify new solutions in order to "finalize the season", by declaring, or not, a champion team, another team for the national phase of Romania's Cup and a county representative for the 3rd league play-off. With the help of statistical information provided by county structures, with the spatial analysis of statistical data reported and analyzed on local and regional level, were analyzed the created situations and, especially, the consequences generated by the pandemic situation upon amateur football in Romania illustrated by maps.